두부손상을 동반한 다발성 외상환자에서 중증도 평가지표로서 염기결핍의 유용성 - 김봉주; 강태경; 최승운; 김혜진; 오성찬; 조석진; 류석용; Kim, Bongjoo; Kang, Taekyung; Choi, Seungwoon; Kim, Hyejin; Oh, Sungchan; et al. (Daehan oe'sang haghoeji, 2012)
Purpose: The arterial base deficit and the serum lactate level are widely recognized indicators of injury severity, adequacy of resuscitation and outcome. The purpose of this study is to evaluate the usefulness of the arterial base deficit as an injury-severity indicator in multiple-trauma patients with head injuries. Methods: Data were retrospectively collected from trauma patients over 18 years of age who had been admitted at the emergency center between October 2005 and July 2006. The patients were divided into head-injury and non-head-injury groups. These patients were then sub-divided into minor ($$ISS{≤_-}15$$)-injury and major ($$ISS{≥_-}16$$)-injury groups according to their injury severity scores (ISS). We analyzed the differences in the base deficits and the serum lactate levels between the major- and the minor-injury sub-groups in both the head-injury and the non-head-injury groups. Results: In the non-head-injury group, we found statistically significant differences in the arterial base deficit between the major-injury and the minor-injury sub-groups($-6.86{±}2.40mmol/L$ vs. $-1.37{±}0.73mmol/L$, p=0.010). In the head-injury group, no significant differences were noted between the two sub-groups($-2.50{±}1.28mmol/L$ vs. $-1.51{±}0.74mmol/L$, p=0.897). Moreover, the differences in arterial base deficit between the major-injury and the minor-injury sub-groups were not significant both for either single-head-trauma or multiple-head-trauma patients (p=0.643 vs. p=0.832). Conclusion: We conclude that neither the arterial base deficit nor the serum lactate level can be used to predict injury severity in multiple-trauma patients with head injuries.